The Results of Search for the Neutrino Magnetic Moment in GEMMA Experiment - A. G. Beda; V. B. Brudanin; V. G. Egorov; D. V. Medvedev; V. S. Pogosov; M. V. Shirchenko; A. S. Starostin (Advances in High Energy Physics)
The result of the neutrino magnetic moment measurement at the Kalinin Nuclear Power Plant (KNPP) with GEMMA spectrometer is presented. The antineutrino-electron scattering is investigated. A high-purity germanium detector with a mass of 1.5 kg placed at a distance of 13.9 m from the 3 GWth reactor core is exposed to the antineutrino flux of 2.7×1013 1/cm2/s. The recoil electron spectra taken in 18134 and 4487 hours for the reactor ON and OFF periods are compared. The upper limit for the neutrino magnetic moment μν<  2.9×10−11μB at 90% C.L. is derived from the data processing.